THE IMPORTANCE OF USING BODY LANGUAGE IN OUR SPEECH FOR TEACHING ENGLISH. (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In English teaching, with the constant reform of teaching methods, body language as a kind of nonverbal language plays a very significant role in the interaction between teachers and students. It not only can express the speakers’ intention more accurately and effectively, simplify the teaching instruction, stimulate the students’ interest, optimize the purpose of English teaching and enhance teaching effectiveness, but also can help improve the students’ ability of listening, speaking, reading and so on. This article discusses how to use body language in English lessons and its value, as well as the secrets of nonverbal communication and useful special strategies that will help you gain confidence and power in any face-to-face interaction. You should also start using your experience to train others and the effect of cultural differences on body language comprehension.